2011
DOI: 10.1007/s11064-011-0448-8
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Plasma Homovanillic Acid Over 13 Months in Patients with Schizophrenia; Relationship with the Clinical Response and the Wisconsin Card Sort Test

Abstract: In the present study we have measured, on a monthly basis, the concentration of plasma homovanillic acid (pHVA) in schizophrenic patients during 13 months of their pharmacological treatment. The average pHVA values of each patient were within the range of 7.30-17.70 ng/ml and the coefficients of variation for each patient (CV %) were within the range of 13-33%. Half of the patients that showed higher pHVA CV% values also showed higher scores on the Brief Psychiatric Rating Scale at the beginning of the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Symptomatic improvement and reaching remission status was most pronounced in FEP patients, as repeatedly reported by other investigators [10,32]. These observations may be related with the individual's state of neuroplasticity, as reflected by the ability to alter pHVA levels, especially since lack of plasticity is hypothesized to be related with loss of antipsychotic efficacy [33,34], poor prognosis and chronic course of disease [12,35]. …”
Section: Discussionsupporting
confidence: 65%
“…Symptomatic improvement and reaching remission status was most pronounced in FEP patients, as repeatedly reported by other investigators [10,32]. These observations may be related with the individual's state of neuroplasticity, as reflected by the ability to alter pHVA levels, especially since lack of plasticity is hypothesized to be related with loss of antipsychotic efficacy [33,34], poor prognosis and chronic course of disease [12,35]. …”
Section: Discussionsupporting
confidence: 65%
“…In a study of schizophrenia patients treated with AAP, HVA levels were found to be increased after treatment [ 49 ]. In the same study, a positive correlation was found between HVA level and PANSS positive subscale [ 50 ]. Plasma HVA levels were found to associate with psychotic symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Plasma HVA levels decreased in the first week of treatment and were correlated with good prognosis [ 53 , 54 ]. In several studies, HVA levels were reported to be positively correlated with clinical improvements in schizophrenia [ 50 ]. In our study, agomelatine significantly decreased HVA levels in the group treated with agomelatine and it was also found that psychotic-like behavior significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups have reported that the blood concentrations of HVA or MHPG were decreased during the psychopathological improvement among patients under an acute state (Bowers et al, 1989; Davidson et al, 1991; Davila et al, 1988; Koreen et al, 1994; Miura et al, 2012 Nagaoka et al, 1997; Pickar et al, 1984; Yoshimura et al, 2010), but these results were not completely consistent in all studies of a similar kind (Zumárraga et al, 2011; Nikisch et al, 2010). Several PET studies demonstrated higher dopamine synthesis within presynaptic dopaminergic neurons in FEP patients and drug-free patients relative to that in a normal control group (Howes et al, 2012), which may partly explain the finding of elevated dopamine turnover at the very early phase as observed in the studies measuring the concentrations of monoamine in patients under FEP (Bowers et al, 1989; Davila et al, 1988; Nagaoka et al, 1997; Pickar et al, 1984).…”
Section: Discussionmentioning
confidence: 94%